Fairness in urban land use: an evolutionary contribution to Law & Economics - Christian Schubert (Max Planck Institute of Economics, 2005)
Markets for complex, multi-faceted goods normally require a complex institutional framework to function properly, i.e., to lead to patterns of outcomes that are deemed acceptable by the individuals involved. This paper examines the institutional underpinnings of the market for urban land use rights, taking both German and U.S. public and private land use law as a case in point. Apart from efficiency considerations that have been discussed in the literature, the individuals' preferences regarding the fairness of (i) the contents of urban land use rights and (ii) the distribution of costs and benefits induced by innovative land uses have been largely neglected. It is argued that investigating the impact of these preferences (and the underlying informal fairness norms) on the legal treatment of land use rights provides a key opportunity to construct an alternative Law & Economics approach that is compatible with an evolutionary perspective on economic land use decisions.
Keywords: K11; R13; R14; 330; externalities; takings; land use law; distributive fairness; procedural fairness